The Interplay of Critical Thinking Explicit Instruction, Academic Writing Performance, Critical Thinking Ability, and Critical Thinking Dispositions: An Experimental Study - Taghinezhad, Ali; Riasati, Mohammad Javad (IJERI: International Journal of Educational Research and Innovation, 2020)
The present study intended to investigate the interplay of critical thinking explicit instruction, academic writing performance, critical thinking ability, and critical thinking dispositions of Iranian students. To this end, 140 students of Jahrom University of Medical Sciences (73 males and 67 females) were selected. They were divided into the experimental and the control groups. Both groups received instruction in academic writing course for 15 weeks 3 hours per week. The students in both groups were administered pre- and post-instruction tests in order to examine the effectiveness of the instruction. Three instruments were utilized in this study including, the researcher-developed essay test, the Ennis-Weir Critical Thinking Essay Test, and the California Critical Thinking Dispositions Inventory (CCTDI). Descriptive statistics and independent-samples t-test were used to analyze the data. The results indicated that there were statistically significant differences between the mean scores of the experimental and the control groups. The results also showed that some CCTDI subscales were not significantly different at the posttest such as, truth-seeking, cognitive maturity, and open- mindedness, whereas the mean posttest scores of other CCTDI subscales were significantly different such as, analyticity, CT inquisitiveness, CT self-confidence, and systematicity. The experimental group had a higher score in the academic writing test compared with the control group. Changes in students’ critical thinking ability, academic writing performance, and their critical thinking dispositions suggest that the CT techniques have been fruitful, and more efforts should be made to integrate the explicit instruction in critical thinking into academic courses.